2017
DOI: 10.3989/mc.2017.07616
|View full text |Cite
|
Sign up to set email alerts
|

New nanomaterials for applications in conservation and restoration of stony materials: A review

Abstract: In recent times, nanomaterials have been applied in the construction and maintenance of the worldÅLs cultural heritage with the aim of improving the consolidation and protection treatments of damaged stone. These nanomaterials include important advantages that could solve many problems found in the traditional interventions. The present paper aims to carry out a review of the state of art on the application of nanotechnology to the conservation and restoration of the stony cultural heritage. We highlight the d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
66
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(86 citation statements)
references
References 118 publications
(160 reference statements)
0
66
0
Order By: Relevance
“…Many works have proven that metallic nanoparticles have powerful antimicrobial, antifungal and antialgae properties. Over the past few years, several experiments with these substances have been carried out for the mitigation of microbial colonization on stone surfaces specially in Cultural Heritage Restoration (Sierra-Fernández et al, 2017). The main limitation for their use is that almost all heavy metals containing these particles are highly toxic for most lifeforms including humans.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…Many works have proven that metallic nanoparticles have powerful antimicrobial, antifungal and antialgae properties. Over the past few years, several experiments with these substances have been carried out for the mitigation of microbial colonization on stone surfaces specially in Cultural Heritage Restoration (Sierra-Fernández et al, 2017). The main limitation for their use is that almost all heavy metals containing these particles are highly toxic for most lifeforms including humans.…”
Section: Nanoparticlesmentioning
confidence: 99%
“…In the case of TEOS-based products, cracking also occurred due to the TEOS/organometallic catalyst ratio [7,8]. As one of the most important drawbacks of alkoxysilanes is the trend to form superficial cracking layers and the lack of penetration through the fissure system of the stone [3][4][5], different strategies have been adopted in the recent years in order to obtain the highest product penetration avoiding surface accumulation, such as the application of nanotechnology to the consolidants' manufacturing [9].…”
Section: Introductionmentioning
confidence: 99%
“…Nanotechnology allows the incorporation of silicon dioxide nanoparticles to consolidants to enhance the dispersion stability and the penetration through fissures [9][10][11]. Zendri et al [11] working with a colloidal suspension of silica nanoparticles of 10-15 nm, sodium silicate and ethyl silicate with calcium carbonate and quartz, found that these consolidants constitute gels of amorphous silica that after the evaporation of the solvent were transformed into xerogels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this sense, a quite valuable effort seems to be provided by nanotechnologies and nanomaterials, recently successfully employed also for stone conservation issues [14]. Among nanoparticles (NPs) based products tested on marbles, nanolime stand out; both commercial and research products have been tested on marbles by monitoring its efficacy both in laboratory condition [5,15,16] and in situ [13,17].…”
Section: Editorialmentioning
confidence: 99%